The impacts of aviation taxation in Ireland - Kelly C. De Bruin; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2021)
The aviation sector has a significant role to play in the reduction of carbon emissions, particularly in light of EU emissions targets. Within the EU, aviation emissions constitute 13.9 per cent of total transport emissions, where under the Green Deal a target of 90 per cent reduction in transport emissions by 2050 has been set. Several tax exemptions apply to the aviation sector due to its international nature, which have contributed to an increasing trend in emissions. Recent movements in EU policy under the 'Fit for 55' package, as well as public and political interest, have focused attention on changing the taxation struc-ture of the aviation industry in order to reduce CO2 emissions. This report focuses on several different potential policies and taxation structures which would attempt to decrease the emissions of the aviation sector: the removal of kerosene taxation exemption (in line with the recent EU proposal), removal of VAT exemption, introduction of a passenger tax, and abolition of free EU ETS allowances by 2026 (in line with the recent EU proposal). Each of these policies, as well a combination scenario, is assessed with respect to the impacts on the aviation industry, spillover effects, macro-economic and government revenue effects, and household effects, as well as the emissions impacts. This analysis applies the Ireland, Environment, Energy and Economy (I3E) model, which allows for the examination of spillover effects of the aviation industry to government, households and other industries. This methodology does not, however, allow for a detailed analysis of different passenger or airline types. In what follows, results are shown as cumulative percentage changes compared to no aviation taxation. Hence a decrease does not present an annual decrease but the build up of a cumulative decrease from 2022 to the given year.
Keywords: 330